Pathomorphological changes in the organs of chickens infected spontaneously by the species Salmonella pullorum on private farms in Chernivtsi region - Shchebentovska, O.; Kostynuk, A.; Zaika, S.; Kovalova, L.; Yevtukh, L.; Holubtsova, M. (Regulatory Mechanisms in Biosystems, 2021)
Commercial poultry production growth and the increase in the number of small farms specializing in raising broiler chickens, laying hens, quails, and other poultry contribute to the spread of infectious diseases. Non-compliance with the principles of biosafety during incubation and breeding results in mass deaths of poultry and, consequently, significant economic losses for farmers. Salmonellosis is one of the most dangerous anthropozoonotic diseases of poultry, which is most often registered in private farms. Age analysis of the poultry salmonellosis in the EU countries indicates the infection of adult laying hens most often, young poultry to a lesser extent, and chickens aged up to 10 days less frequently. Although the program for the prevention and elimination of poultry salmonellosis has been approved at the legislative level in Ukraine, monitoring studies are not carefully conducted. This is especially true for private homesteads and small farms, which greatly complicates the epizootiological situation in some regions of the country. The article describes the pathological and histological changes in the liver, heart, lungs, kidneys, and spleen. The changes were detected in chickens aged 10 and 14 days infected with microorganisms of the species Salmonella pullorum. Eggs for incubation were obtained from different family flocks, and incubation was performed in a single incubator. The initial clinical signs of the disease appeared in chickens aged 7 days and included diarrhea, increased water consumption, lameness, mass concentration of chickens near heat sources, nervous phenomena in the form of circle walking, and partial blindness in some cases. The pathological autopsy revealed hepatomegaly with sharp change in the organ colour, diapedetic hemorrhage under Glisson’s capsule, and diffuse miliary necrosis. Greyish-white nodular lesions of the lungs and heart, dystrophic changes in the kidneys, and deposition of uric acid salts in the ureters were also characteristic features. Diffuse coagulation necrosis, massive perivascular infiltration by heterophilic lymphocytes and stasis were observed in the liver. Changes in the heart were characterized by significant infiltration by mononuclear cells and heterophiles, which led to atrophy, necrosis, and replacement of cardiomyocytes by connective tissue cellular elements. Delymphatization and necrosis of the lymph nodes were pronounced in the spleen.